2018
DOI: 10.5704/moj.1811.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome after Treatment of Aggressive Tumours in the Distal Radius: Comparison between Reconstruction using Proximal Fibular Graft and Wrist Fusion

Abstract: Introduction: Restoration of a functional hand is the ultimate goal following a distal radius tumour resection. The early outcomes of mobile wrist reconstruction are satisfactory; however, long-term results are unpredictable due to late wrist instability and degenerative arthritis. Our aim is to compare mobile wrist reconstruction with wrist fusion (pan-carpal fusion) in our cohort of patients.Materials and Methods: A retrospective cohort study was performed for functional outcomes of all patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Recent literature has shown that there is no difference in long-term functional outcome between reconstruction and fusion group [2]. Translocations of ulna, wrist arthrodesis using segmental iliac crest graft and complex procedure of segmental double barrel ulnar graft arthrodesis with Sauve-Kapandji procedure also produce equally long-term outcome [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent literature has shown that there is no difference in long-term functional outcome between reconstruction and fusion group [2]. Translocations of ulna, wrist arthrodesis using segmental iliac crest graft and complex procedure of segmental double barrel ulnar graft arthrodesis with Sauve-Kapandji procedure also produce equally long-term outcome [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Joint reconstruction after resection of aggressive tumors remains a popular alternative in order to reduce the local recurrence rate while maintain wrist motion and ideally improving function compared to arthrodesis. The use of free vascularized proximal fibula graft is attractive because of its similarity in shape to the distal radius [2]. However, some major postoperative complications were reported including progressive degenerative changes, bony collapse secondary to poor vascularity of the fibular head, and volar subluxation resulting from incongruity between the fibular head and the proximal carpal row.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wrist arthroplasty using proximal fibular head arthroplasty [21,23,32], osteoarticular grafting [7,22,25], or prosthetic hemiarthroplasty [14,30] offers the advantage of wrist movement but carries an associated risk of wrist subluxation, pain, and limited pronosupination [7, 14, 21-23, 30, 34]. Wrist fusion using an autograft [5,23,27] or allograft [28] provides long-term wrist stability at the cost of movement. Recent publications have shown that wrist fusion is superior to other reconstruction options in the distal radius [5,21,29].…”
Section: Introductionmentioning
confidence: 99%